A mechanism‐based pharmacokinetic model of remdesivir leveraging interspecies scaling to simulate COVID‐19 treatment in humans - Patrick O. Hanafin; Brian Jermain; Anthony J. Hickey; Alexander V. Kabanov; Angela DM. Kashuba; Timothy P. Sheahan; Gauri G. Rao (Wiley, 2021)
Abstract The severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) outbreak initiated the global coronavirus disease 2019 (COVID‐19) pandemic resulting in 42.9 million confirmed infections and > 1.1 million deaths worldwide as of October 26, 2020. Remdesivir is a broad‐spectrum nucleotide prodrug shown to be effective against enzootic coronaviruses. The pharmacokinetics (PKs) of remdesivir in plasma have recently been described. However, the distribution of its active metabolite nucleoside triphosphate (NTP) to the site of pulmonary infection is unknown in humans. Our objective was to use existing in vivo mouse PK data for remdesivir and its metabolites to develop a mechanism‐based model to allometrically scale and simulate the human PK of remdesivir in plasma and NTP in lung homogenate. Remdesivir and GS‐441524 concentrations in plasma and total phosphorylated nucleoside concentrations in lung homogenate from Ces1c−/− mice administered 25 or 50 mg/kg of remdesivir subcutaneously were simultaneously fit to estimate PK parameters. The mouse PK model was allometrically scaled to predict human PK parameters to simulate the clinically recommended 200 mg loading dose followed by 100 mg daily maintenance doses administered as 30‐minute intravenous infusions. Simulations of unbound remdesivir concentrations in human plasma were below 2.48 μM, the 90% maximal inhibitory concentration for SARS‐CoV‐2 inhibition in vitro. Simulations of NTP in the lungs were below high efficacy in vitro thresholds. We have identified a need for alternative dosing strategies to achieve more efficacious concentrations of NTP in human lungs, perhaps by reformulating remdesivir for direct pulmonary delivery.